PEMANFAATAN ENZIM PAPAIN KASAR DALAM UPAYA MENINGKATKAN KUALITAS DAGING KUDA TUA AFKIR DI KABUPATEN HUMBANG HASUNDUTAN - wiwiet gesty utami (Universitas Sumatera Utara, 2014)
Meat of old horse have tough characteristics, so we need to improve the quality of horse meat tenderness. This study aimed to determine the effect of incubation crude papain enzyme on tenderness, pH, cooking loss, water holding capacity, and organoleptic, total microba. This research was conducted at the Laboratory of Food Technology Faculty of Agriculture, University of Sumatera Utara in July - August 2013. The design used in this study was factorial complete randomized design (CRD factorial) using two factors such as: the concentration of the crude papain enzyme (A): (0, 0,25 ml/g and 0,5 ml/g, respectively) and incubation time (B): (60, 90 and 120 min, respectively). The variables were analyzed consist of tenderness, pH, cooking loss, water holding capacity, organoleptic test (texture, juiciness, flavor and tenderness) and total microba. The results showed that the concentration of the crude papain enzyme had high significantly different (P<0.01) effect on the tenderness, cooking loss, water holding capacity and organoleptic test. While the incubation time showed significantly different (P<0.05) effect on tenderness organleptic test. It is concluded that the best concentration of the crude papain enzyme is 0,5ml/g with incubation time of 120 minutes. Keywords : Crude Papain Enzyme, Quality, Horse Meat, Organoleptic.